Sistem Pendukung Keputusan Pemilihan Dosen Berprestasi dengan Metode Profile Matching di Lingkungan Poltekkes Kemenkes Padang - Yuniko Fauzan; Y Yuhandri (Jurnal Sistim Informasi dan Teknologi, 2019)
The Polytechnic of the Ministry of Health of the Republic of Indonesia in Padang always conducts an annual assessment of outstanding lecturers. In terms of assessment, it must be based on the Tri Dharma of Higher Education which includes performance as well as personality and social achievements. The process of selecting outstanding lecturers at the Padang Ministry of Health Poltekkes is still manual, therefore it is necessary to design an application of a decision support system to determine outstanding lecturers using computerization using the profile matching method. The application is expected to help the campus in making decisions regarding the determination of outstanding lecturers with predetermined criteria and values. The results of this study get the final value of 4.84 obtained by the lecturer Dosen 2. Then from this analysis will be able to help the campus in determining the outstanding lecturers.